2017
DOI: 10.1007/s12594-017-0714-8
|View full text |Cite
|
Sign up to set email alerts
|

Study of Mechanical Properties of Vindhayan Shaly Rocks at Elevated temperature

Abstract: Shale is an important rock due to its suitability for different engineering and scientific applications. Elevated temperature may cause major deformation or damage in shale rock and it may be of irreversible in nature. Such damage have adverse effect on the physicomechnical properties of shale rock. The uniaxial compressive strength and tensile strength of two shales (upper Vindhyan basin, India) have been estimated at elevated temperature using point load strength index method. The rock samples have been anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…In recent decades, several studies have focused on understanding the mechanical behavior of progressive damage and microscopic damage mechanisms of rocks under various temperature–pressure coupling conditions using experimental and numerical simulation techniques 10–15 . These studies were conducted to investigate the microscopic mechanisms of complex macroscopic properties of rock materials and establish theories and methods for cross‐scale correlation and multi‐scale analyses of macroscopic and microscopic properties.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent decades, several studies have focused on understanding the mechanical behavior of progressive damage and microscopic damage mechanisms of rocks under various temperature–pressure coupling conditions using experimental and numerical simulation techniques 10–15 . These studies were conducted to investigate the microscopic mechanisms of complex macroscopic properties of rock materials and establish theories and methods for cross‐scale correlation and multi‐scale analyses of macroscopic and microscopic properties.…”
Section: Introductionmentioning
confidence: 99%
“…under various temperature-pressure coupling conditions using experimental and numerical simulation techniques. [10][11][12][13][14][15] These studies were conducted to investigate the microscopic mechanisms of complex macroscopic properties of rock materials and establish theories and methods for cross-scale correlation and multi-scale analyses of macroscopic and microscopic properties. Among them, the experimental studies generally combined tri-axial compression tests with microscopic monitoring methods (acoustic emission, scanning electron microscopy, and computed tomography (CT)) to characterize and analyze the progressive evolution of cracks.…”
mentioning
confidence: 99%
“…They reported that with increasing temperature, Young's modulus and the compressive failure strength decreased significantly, but the overall deformability and the nonlinearity of the failure surface increased gradually. Jha et al (2015Jha et al ( , 2017 studied the effects of thermal treatment on the physical and mechanical properties of two types of Indian shale and discovered that the porosity of the two shales significantly increased with increasing temperature, whereas the density and the uniaxial compressive and tensile strength of the two shales decreased in varied magnitudes. Mohamadi and Wan (2016) conducted hightemperature triaxial compression tests on shale specimens with horizontal bedding planes and found that shale specimens exhibited a considerable degree of strain-softening brittleness under low confining pressure.…”
Section: Introductionmentioning
confidence: 99%
“…Mohamadi et al [18] conducted a series of triaxial tests on shale at different temperatures and discussed in detail the influence of temperature on shale strength. Jha et al [19] conducted uniaxial compression tests and tensile strength tests at different temperatures from normal temperature to 900°C and studied in detail the influence of high temperature on the physical and mechanical properties and uniaxial compressive strength of shale. Rybacki et al [20] conducted creep tests on shale with different temperatures (50~200°C) and different confining pressures (50~200 MPa) to study the influence of temperature and confining pressure on creep characteristics.…”
Section: Introductionmentioning
confidence: 99%